Pengaruh Penggunaan Media Busy Book Terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun Di Taman Kanak-Kanak Yayasan Amalan Parupuk Tabing - Fitasari, Nur; Wirman, Asdi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
This study aims to determine the effect of the use of busy book media on the fine motor skills of children aged 5-6 years at the Kindergarten of the Amalan Parupuk Tabing Foundation, Tabing Kec. Koto Tangah, the city of Padang, West Sumatra, academic year 2022/2023. This research is a quantitative research with pre-experimental methods, with pretest and posttest designs. Pretest posttest one group design which was carried out twice, namely before and after the experiment. The data collection technique in this study was in the form of fine motor activity observation sheets (pretest) and a fine motor assessment indicator rubric (post test). The subjects of this study were students aged 5-6 years at the Kindergarten of the Tabing Prapuk Foundation, Kec. Koto Tangah, the city of Padang, West Sumatra, with a population of 13 children. In taking the sample, the researcher used a purposive sampling technique so that the number of samples was 10 people. The results showed that there was an influence from the use of busy book media on the fine motor development of children aged 5-6 years where before using the busy book media the children's fine motor skills at the initial score (pretest) were 140 and at the final score (post test) 197 this shows an increase between initial test and post test, the results of the hypothesis test also show that the probability is greater 0.131> 0.05 then Ha is accepted. So it can be concluded that the use of busy book media can affect the fine motor skills of children aged 5-6 years in the Kindergarten of the Amalan Parupuk Tabing Foundation, Tabing Kec. Koto Tangah is the city of Padang, West Sumatra